Pendekatan Proses dalam Pembelajaran Psikologi Pendidikan Berbasis Digital di Era Society 5.0 - Yanah; Kunti Malika; Siti Nur Halisaturrohma; Nur Eisyatur Rodliyah; Ivo Sindia Nur Azizah (Al-Kindi, 2026)
The rapid development of digital technology and the emergence of the Society 5.0 era have encouraged a transformation in learning paradigms toward student-centered and technology-integrated education. This study aims to examine the concept of the process approach in digital-based Educational Psychology learning, its implementation in the Society 5.0 era, and the advantages, challenges, and solutions that support its effectiveness. The study employed a Systematic Literature Review (SLR) method by reviewing relevant journal articles, books, conference proceedings, and other scholarly sources related to the process approach, Educational Psychology, digital learning, and Society 5.0. Data were analyzed using thematic analysis to identify major themes emerging from the literature. The findings indicate that the process approach positions learners as active participants in observing, questioning, gathering information, analyzing data, and drawing conclusions, thereby enhancing critical thinking, creativity, problem-solving skills, and independent learning. The implementation of a digital-based process approach is supported by the use of Learning Management Systems (LMS), interactive digital media, and collaborative platforms that expand learning accessibility and improve instructional interaction. However, several challenges remain, including limited technological infrastructure, digital access disparities, and uneven digital competencies among educators and learners. Therefore, strengthening digital literacy, developing innovative learning media, enhancing educators’ competencies, and improving technological infrastructure are essential to achieving effective, inclusive, and sustainable learning. This study highlights that the digital-based process approach plays a strategic role in fostering 21st-century competencies and supporting educational goals aligned with the demands of Society 5.0.